Bacterial cell-to-cell signaling promotes the evolution of resistance to parasitic bacteriophages - Moreau, Pierre; Diggle, Stephen P.; Friman, Ville-Petri (Wiley, 2017)
The evolution of host–parasite interactions could be affected by intraspecies variation between different host and parasite genotypes. Here we studied how bacterial host cell-to-cell signaling affects the interaction with parasites using two bacteria-specific viruses (bacteriophages) and the host bacterium Pseudomonas aeruginosa that com- municates by secreting and responding to quorum sensing (QS) signal molecules. We found that a QS-signaling proficient strain was able to evolve higher levels of resist- ance to phages during a short-term selection experiment. This was unlikely driven by demographic effects (mutation supply and encounter rates), as nonsignaling strains reached higher population densities in the absence of phages in our selective environ- ment. Instead, the evolved nonsignaling strains suffered relatively higher growth re- duction in the absence of the phage, which could have constrained the phage resistance evolution. Complementation experiments with synthetic signal molecules showed that the Pseudomonas quinolone signal (PQS) improved the growth of nonsignaling bacteria in the presence of a phage, while the activation of las and rhl quorum sensing systems had no effect. Together, these results suggest that QS-signaling can promote the evo- lution of phage resistance and that the loss of QS-signaling could be costly in the pres- ence of phages. Phage–bacteria interactions could therefore indirectly shape the evolution of intraspecies social interactions and PQS-mediated virulence in P. aeruginosa.